Adjustment of Students in Boarding Houses (Descriptive-Comparative Study of Students from Outside and in Sumatera Barat) - Sindi Mayesti; Asmidir Ilyas (Jurnal Neo Konseling, 2019)
The meaning of educational success someone discusses about what has been obtained can help those who are completed adjust to their needs and restore their living environment. Every student should be able to adjust wherever he is, but still there are still students who have not been able to work alone in a boarding house. This research is a descriptive-comparative research with quantitative methods. The research subjects selected 100 Padang State University students selected using purposive sampling and incidental sampling techniques. The research instrument used was a questionnaire with a Likert scale model. The results of the study revealed: (1) Distributed to students from West Sumatra in accordance with the fairly good category (2) Self-readable with students issued from outside West Sumatra according to the fairly good category (3) Obtained from significant amounts according to others UNP boarding students from outside and in West Sumatra. Based on the findings, it is recommended that counselors / counselors from outside the school be able to provide guidance and counseling services, namely conversation services, information services, individual counseling services and group guidance services in order to assist students in increasing direct assistance in boarding houses.